Anti-tumour necrosis factor-alpha agent therapy, compared with conventional therapy, reduces the relapse of uveitis in patients with behçet’s disease: A systematic review of controlled trials - Zhou, Xinwei; Shi, Xianghui; Ren, Yanxia; Yan, Tingting; Ye, Qiao (Frontiers in Pharmacology, 2022)
Purpose: Anti-tumour necrosis factor-alpha (TNF-α) agents are often used for Behçet’s disease (BD) in clinical practice, but they have not been validated by a high level of evidence. We systematically reviewed published controlled trials to investigate the efficacy and safety of anti-TNF-α therapy and summarize the efficacy of anti-TNF-α therapy relative to the available therapeutic options. Methods: A systematic database search was conducted (PubMed, Embase and Cochrane) using specific search terms. All controlled studies of anti-TNF-α treatment of BD patients prior to December 2021 were included. Single-arm studies were excluded. The decision of whether to incorporate data into the meta-analysis or summarize the data by qualitative synthesis was based on the results of the literature screening. Results: Of 4389 screened studies, 13 (total 778 patients) were included in accordance with our retrieval strategy, comprising 1 randomized controlled trial, 1 prospective study, 10 retrospective studies, and 1 multicentre open-label study. Ten studies (76.9%) involved Behçet’s uveitis (BU), 1 involved intestinal BD, and the other studies had undefined subtypes. Subgroup reviews were conducted according to the control drug. Four studies involving 167 participants reported relapse rates. Meta-analysis of three of these studies demonstrated that, compared with traditional immunosuppressant (TIS) therapy, anti-TNF-α therapy reduced the relapse rates in patients with BU. In targeted drug comparison studies, the efficacy appeared to be similar between the anti-TNF-α agent and interferon in BU patients. The rates of adverse events were comparable between a variety of different therapeutic controls. Serious adverse events were not observed in 53.8% (7/13) of the studies. Conclusions: Compared with TIS therapy, anti-TNF-a therapy reduces the relapse of uveitis in patients with BD. However, the evidence regarding anti-TNF-α therapy is very limited for the full spectrum of BD subtypes, which calls for caution.